Using meteorology probability forecasts in operational hydrology - Croley, Thomas E. (ASCE Press, 2000)
"This book presents theory, procedures, and examples for using short-term, seasonal, and interannual forecasts of meteorology probabilities, available every day from the National Oceanic and Atmospheric Administration, Environment Canada, other agencies, and the user. The heuristic approach simultaneously uses forecasts over different time scales, time periods, spatial domains, probability statements, and meteorology variables. The book describes the generation of consequent hydrology (or other) probability forecasts, via operational hydrology methods, for assessing decision risks associated with uncertain meteorology. Any hydrology (or other) model may be used, as illustrated herein. Freely available graphical user interface software is documented to use intuitively and easily the multitude of probabilistic meteorology outlooks available."